The adventures of Sherlock Holmes - Doyle, Arthur Conan (Oxford University Press, 1992)
For generations, readers have enjoyed classic literature. They have delighted in the romance of Jane Austen, thrilled at the adventures of Jules Verne, and pondered the lessons of Aesop. Introduce young readers to these familiar volumes with Great Illustrated Classics. In this series, literary masterworks have been adapted for young scholars. Large, easy-to-read type and charming pen-and-ink drawings enhance the text. Students are sure to enjoy becoming acquainted with traditional literature through these well-loved classics